2020
DOI: 10.3390/genes11020147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Castration on miRNA, lncRNA, and mRNA Profiles in Mice Thymus

Abstract: Thymic degeneration and regeneration are regulated by estrogen and androgen. Recent studies have found that long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) are involved in organ development. In this study, RNA sequencing (RNA-seq) results showed that ovariectomy significantly affected 333 lncRNAs, 51 miRNAs, and 144 mRNAs levels (p < 0.05 and |log2fold change| > 1), and orchiectomy significantly affected 165 lncRNAs, 165 miRNAs, and 208 mRNA levels in the thymus. Gene Ontology (GO) and Kyoto Encycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…Therefore, inadequate production or malfunctioning of IFNs favors the existence of the virus in the host. Among various isoforms of INF, INFα has shown antiviral effects against the SARS-CoV virus, whereas INFβ demonstrated an antiviral effect for both SARS and MERS viruses [ 74 ]. The functional relationship between the thymus and different cytokines, including INFs, has shown that thymic cells can initiate the production of cytokines [ 75 ].…”
Section: Cytokines Activity Against Coronavirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inadequate production or malfunctioning of IFNs favors the existence of the virus in the host. Among various isoforms of INF, INFα has shown antiviral effects against the SARS-CoV virus, whereas INFβ demonstrated an antiviral effect for both SARS and MERS viruses [ 74 ]. The functional relationship between the thymus and different cytokines, including INFs, has shown that thymic cells can initiate the production of cytokines [ 75 ].…”
Section: Cytokines Activity Against Coronavirusesmentioning
confidence: 99%
“…On the other hand, SARS-CoV epitopes of the T and B lymphocytes were thoroughly mapped to analyze the humoral immune responses and the production of different antibodies against a particular virus strain [ 4 ]. It has been observed that the total time needed for a specific antibody to develop and can be detected in the serum was 4 to 14 days [ 74 ]. Additionally, the antibody produced in a long-lasting stage, about two years, is the IgG-neutralizing antibody.…”
Section: Role Of the Thymus In Humoral Immunity Against Coronavirusmentioning
confidence: 99%
“…After 17-estradiol (E2) stimulation, the differentially expressed lncRNAs are predicted to be mainly involved in cell cycle and apoptosis in mTECs, like Gm26870 and TCONS_00067179 [ 84 ]. Correspondingly, lncRNAs expression is also widely affected after ovariectomy or orchiectomy, like lnc191945, lnc180466 and lnc186500 [ 85 ]. Taken together, those studies suggest that lncRNA may govern the proliferation of TECs and physiological aging processes by regulating the expression of miRNA or transcription factors.…”
Section: Epigenetic Modification Of Tecs In Thymus Atrophymentioning
confidence: 99%
“…Nevertheless, only a few lncRNAs have functional annotations [14] . In a previous study, we identified 17498 lncRNAs in the mouse thymus and found that 64 lncRNAs might participate in castration-regulated thymic involution through ceRNA [15] . However, the understanding of lncRNAs regulating thymic involution is still not clear.…”
Section: Introductionmentioning
confidence: 99%